Indeks Kerentanan Seismik Menggunakan Data Mikrotremor untuk Daerah Perbukitan dan Pemukiman di Bukit Nobita Kota Padang - Anjelina, Fani; Pohan, Ahmad Fauzi (Jurnal Fisika Unand, 2024)
Research on the seismic vulnerability index on Nobita Hill, Padang City uses the microtremor method. The study was conducted in two areas, namely hilly and residential areas around Nobita Hill. Measurements were carried out using a geophone with three components, a north-south horizontal component, an east-west horizontal component and an up-down vertical component at 7 points in hilly areas and 9 points in residential areas with a recording duration of 30 minutes. The measurement results were then processed using the Horizontal Vertical Spectral Ratio (HVSR) method using Geopsy software and mapped using Surfer 11. The research results show that the Nobita Hill area and the settlements around the hill are not vulnerable to seismicity because both research areas have a small category of seismic vulnerability index. This is characterized by dominant frequency values in the hills ranging from 0.633 - 0.935 Hz, amplification from 0.905 - 1.306, and seismic vulnerability index from 1.234 - 2.622. In residential areas, dominant frequency values were found ranging from 0.645 - 2.983 Hz, amplification from 1.109 - 1.316, and seismic vulnerability index from 0.438 - 1.974. This indicates that both studies are safe in the event of an earthquake.